Les projets urbains en zones inondables communiquent-ils sur les risques ? - Sylvain Dournel; Mathilde Gralepois; Johnny Douvinet (Belgeo, 2015)
The paper draws the links between flood management and risk communication concerning planning policies and especially urban projects. We investigate three French sites along the Loire valley: Saint-Étienne, Orléans and Nantes. For this purpose, spatial multiscalar analysis gives an overview on the potential contradictions and loss of information between risk communication, spatial planning and urban projects. We demonstrate that regardless of demographic and economic trends, the city is spreading and taking over flooding areas. The principle of living with risk is a reality that the urban actors seem to accept. However, the integration of the risk in the urban policies is incomplete and heterogeneous. In this context, the paper will try to highlight these important discrepancies which appear in communication policies. If intermunicipal structures are developing new communication tools about flood risk, much remains to be done to alert the residents to this situation. In fact, flood risk seems to be ignored in urban construction at local scale.